2022
DOI: 10.1155/2022/1244660
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Enterprise Human Resource Optimization Algorithm Using PSO Model in Big Data and Complex Environment

Abstract: The distribution of human resources has a direct impact on the HR utilization rate in businesses, which in turn has an impact on the profitability and labor productivity of those businesses. As a result, this article develops an enterprise HR optimal allocation model based on PSO. The concepts of HR and HR allocation are introduced, and a programme for implementing optimal HR allocation in businesses is provided from the perspectives of scale prediction, structure analysis, and implementation. An HR configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In this case, big data makes HR management easier because employee data is collected, organized, and analyzed quickly (X. Wang & Zhang, 2022). Interestingly, the recruitment process takes place more objectively by using big data (Hoang et al, 2018).…”
Section: Recruitment Efficiencymentioning
confidence: 99%
“…In this case, big data makes HR management easier because employee data is collected, organized, and analyzed quickly (X. Wang & Zhang, 2022). Interestingly, the recruitment process takes place more objectively by using big data (Hoang et al, 2018).…”
Section: Recruitment Efficiencymentioning
confidence: 99%
“…The study by Wang & Zhang (2022) develops an optimal human resource allocation model based on PSO, the methods of system, and quantitative evaluation. The author believes that the distribution of human resources has a direct effect on the efficiency of human resource utilization in enterprises, which in turn has a strong impact on profits and labor productivity.…”
Section: Research Overviewmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%